1996
DOI: 10.1007/bf00035372
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic solution for mode III crack growth in J 2-elastoplasticity with mixed isotropic-kinematic strain hardening

Abstract: Mode III fracture propagation is analyzed in a J2-flow theory elastoplastic material characterized by a mixed isotropic/kinematic law of hardening. The asymptotic stress, back stress and velocity fields are determined under small-strain, steady-state, fracture propagation conditions. The increase in the hardening anisotropy is shown to be connected with a decrease in the thickness of the elastic sector in the crack wake and with an increase of the strength of the singularity. A second order analytical solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…The problem of mode III crack propagation within the classical J 2 -flow theory was first analysed by Amazigo and Hutchinson (1977) and Ponte Castañeda (1987) for materials which display linear and isotropic hardening and extended by Bigoni and Radi (1996) to mixed isotropic/kinematic hardening. These investigations found that the strength of the stress singularity turns out to be extremely weak for the typically small values of the strain hardening for ductile metals.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of mode III crack propagation within the classical J 2 -flow theory was first analysed by Amazigo and Hutchinson (1977) and Ponte Castañeda (1987) for materials which display linear and isotropic hardening and extended by Bigoni and Radi (1996) to mixed isotropic/kinematic hardening. These investigations found that the strength of the stress singularity turns out to be extremely weak for the typically small values of the strain hardening for ductile metals.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the solution obtained for conventional elastic-plastic response predicts a weak stress singularity for small strain-hardening, which becomes vanishing small in the limit case of elastic-perfectly plastic behavior of the material, namely for α = 0. The curves plotted in Figures 2b and 3b show that the displacements ahead and behind the crack-tip are opposite in sign, unlike the classical Mode III crack-tip fields in non-polar materials [19][20][21]. Similar results have been also obtained for a Mode III crack both for CS elastic [23] and CS elastic-plastic material behavior [26].…”
Section: Resultssupporting
confidence: 72%
“…The problem of Mode III crack propagation in ductile materials was first analyzed within the classical J 2 -flow theory for linear and isotropic hardening [19,20] and extended to mixed isotropic/kinematic hardening [21]. These investigations found that the strength of the stress singularity turns out to be extremely weak for small strain hardening.…”
Section: Introductionmentioning
confidence: 99%